Pencarian Dokumen Jurnal Skripsi Dengan Menggunakan Metode Positive Impact Factor Query (PIFQ) - Tutuk Indriyani; Septiyawan Rosetya Wardhana; Muhammad Fakhrul Amin (Institut Teknologi Adhi Tama Surabaya, 2023)
ABSTRACT To facilitate the search for student thesis journals using an information retrieval system, users are made easy in finding information from a large amount of data. Information retrieval in the current era has been widely applied in various fields, such as information on the internet and also information stored locally. Document search is one of the implementations of using information retrieval. proposed a new weighting method on words based on Positive Impact Factor Query (PIFQ). The result is that calculations using the PIFQ method can outperform calculations using the TF-IDF method. How can the PIFQ method be applied to an information retrieval system for searching Informatics Engineering thesis documents that match the queries and topics entered by the user. The goal is to find the thesis document that matches the query entered by the user. The benefit is as a means for Informatics Engineering students at the Adhi Tama Surabaya Institute of Technology in finding thesis documents that are appropriate to their topic. a system designed to recommend ITATS student journal data using the Term Frequency - Inverse Document Frequency and Positive Impact Factor Query methods is proven to be able to produce relevant search results for users with the highest rating rating of 13.38. In the third test scenario, several journals get a value of 0 for calculations using the TF-IDF method. This is of course a deficiency in the system that has been designed because it is not in accordance with the wishes of the researcher.Keywords: Information retrieval; Positive Impact Factor Query; Term Frequency - Inverse Document Frequency ABSTRAK Untuk memudahkan dalam pencarian jurnal skripsi pada mahasiswa menggunakan sistem temu kembali informasi, pengguna dimudahkan dalam menemukan suatu informasi dari data yang sangat banyak. Information retrieval pada era sekarang telah banyak diterapkan pada berbagai bidang, seperti informasi dalam jaringan internet dan juga informasi yang tersimpan secara lokal. Pencarian dokumen merupakan salah satu dari implementasi penggunaan information retrieval. diusulkan sebuah metode pembobotan baru pada kata yang bebasis Positive Impact Factor Query (PIFQ). Hasilnya perhitungan dengan menggunakan metode PIFQ dapat mengungguli perhitungan dengan menggunakan metode TF-IDF. Bagaimana metode PIFQ dapat diterapkan pada sistem temu kembali informasi untuk pencarian dokumen skripsi Teknik Informatika yang sesuai dengan query dan topik yang dimasukkan oleh pengguna. Tujuannya untuk mencari dokumen skripsi yang sesuai dengan query yang dimasukkan oleh pengguna. Manfaatnya sebagai sarana untuk mahasiswa Teknik Informatika Intitute Teknologi Adhi Tama Surabaya dalam mencari dokumen skripsi yang sesuai dengan topiknya. sistem yang dirancang untuk merekomendasikan data jurnal mahasiswa ITATS menggunakan metode Term Frequency - Inverse Document Frequency dan Positive Impact Factor Query terbukti mampu menghasilkan hasil pencarian yang relevan bagi pengguna dengan nilai tertinggi dari perengkingannya 13.38. Pada skenario pengujian yang ketiga, beberapa jurnal mendapatkan nilai 0 untuk perhitungan dengan menggunakan metode TF-IDF. Hal ini tentun saja menjadi kekurangan pada sistem yang telah dirancang karena tidak sesuai dengan keinginan peneliti.Kata kunci: Information retrieval; Positive Impact Factor Query; Term Frequency - Inverse Document Frequency;